Taxonomic revision of the antlion genus Cueta Navás, 1911 (Neuroptera: Myrmeleontidae: Myrmeleontinae) from Pakistan. (3rd April 2023) - Hassan, Muhammad Asghar; Zheng, Yuchen; Zia, Ahmed; Liu, Xingyue
ABSTRACT: Taxonomic revision of the genus Cueta Navás from Pakistan is presented by redescribing four of the five species, i.e., C. facile, C. infensa, and C. minervae in this country. Cueta omana syn. nov . is proposed as a junior synonym of Cueta thaliae, a poorly known species, only documented from Afghanistan and Pakistan. Cueta infensa is reported as a new record for Pakistan. The holotype photographs of Cueta infensa and Cueta omana are also presented. Distributional maps, a comprehensive list of synonyms, diagnostic characters for each studied species, and a key to species based on adult characters are provided.